2021
DOI: 10.52547/jech.8.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Internet Addiction and Identity Styles in Bushehr University of Medical Sciences Students

Abstract: Relationship between internet use and academic achievement ... [3] The relationship between internet and cell-phone addictions ... [4] Assessment of internet addiction among college students ... [5] Ego identity status and identity processing orientation ... [6] Modeling structural relations of social support ... [7] Identity styles and academic status of Gilan university ... [8] Relationship between internet addiction and depression ... [9] The relationship between internet addiction and personality ... [10]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…32 In a study conducted by Long et al 34 , majoring in science vs. humanities was a significant predictor of problematic smartphone use in the final model (OR = 2.14, p-value < 0.001). Moreover, Zarei et al 33 found that 90.2% of medical sciences students were not addicted to their smartphones and that only 9.8% were addicted to the internet. Specifically, when considering subelements, including entertainment, educational, and financial use, the findings indicated that students in the HSS field are more likely to use smartphones to accomplish various daily tasks than students in other fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In a study conducted by Long et al 34 , majoring in science vs. humanities was a significant predictor of problematic smartphone use in the final model (OR = 2.14, p-value < 0.001). Moreover, Zarei et al 33 found that 90.2% of medical sciences students were not addicted to their smartphones and that only 9.8% were addicted to the internet. Specifically, when considering subelements, including entertainment, educational, and financial use, the findings indicated that students in the HSS field are more likely to use smartphones to accomplish various daily tasks than students in other fields.…”
Section: Discussionmentioning
confidence: 99%
“…A self-administered questionnaire developed and created by the researchers was based on a survey of relevant literature and similar studies. 3,5,6,32,33 The questionnaire consisted of three different sections. The first section comprised 10 items describing the demographic characteristics of the participants, including fields of study, gender, age, body mass index (BMI), underlying diseases, father's occupation, mother's occupation, financial status (financial support from parents), smartphone experience, and internet usage patterns.…”
Section: Instrumentationmentioning
confidence: 99%